2000
DOI: 10.1177/0957926500011004003
|View full text |Cite
|
Sign up to set email alerts
|

Presentations of Romanies in the Czech Media: On Category Work in Television Debates

Abstract: This article concerns categorizations of Romanies in Czech media. We analysed four television debates which were broadcast in the Czech Republic between 1990 and 1995. All of them concerned Romanies, and Czechs and Romanies participated in each of them. The analytic technique we used was membership categorization analysis (MCA), associated with Sacks (1992), and with contemporary ethnomethodology. Our analysis focused on how descriptions of Romanies were used and warranted, and how the membership categorizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 12 publications
3
47
0
4
Order By: Relevance
“…People engaged in conversations about themselves and others construct and negotiate categorial meanings and the 'reality' that they are talking about. Studies of the ways in which ethnic minorities define and account for their identity (especially to members of their own group) are still relatively scarce (but see Leudar and Nekvapil, 2000;Verkuyten, 1997Verkuyten, , 2005Verkuyten and de Wolf, 2002). Perhaps the most interesting and insightful study on the topic is Verkuyten and de Wolf's (2002) that shows how ethnic minority members (Chinese residents in the Netherlands) construct different versions of identity in interactions with members of their own group through mobilizing various discursive and cultural resources, and offering both deterministic and agentic accounts of their identity as minority group members.…”
Section: Studying Identity In Theory and In Actionmentioning
confidence: 99%
“…People engaged in conversations about themselves and others construct and negotiate categorial meanings and the 'reality' that they are talking about. Studies of the ways in which ethnic minorities define and account for their identity (especially to members of their own group) are still relatively scarce (but see Leudar and Nekvapil, 2000;Verkuyten, 1997Verkuyten, , 2005Verkuyten and de Wolf, 2002). Perhaps the most interesting and insightful study on the topic is Verkuyten and de Wolf's (2002) that shows how ethnic minority members (Chinese residents in the Netherlands) construct different versions of identity in interactions with members of their own group through mobilizing various discursive and cultural resources, and offering both deterministic and agentic accounts of their identity as minority group members.…”
Section: Studying Identity In Theory and In Actionmentioning
confidence: 99%
“…Second, Leudar and Nekvapil (2000) look at how Czech Romanies are presented in television debates. Turner's (2000) paper Gypsies and Politics in Britain, examines the treatment of Gypsies in politics and this includes an analysis of some of the things that Jack Straw has said about Gypsies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The reader of the article firstly does not know the truth of the situation, and secondly becomes complicit in the normalisation of discriminatory discourse. Leudar and Nekvapil (2000) also looked at the representation of Romanies, but this time in Czech television debates. They examined conversations in debates between Czechs and Romanies and found that many descriptions were used and they were warranted as common sense, or universal truths.…”
mentioning
confidence: 99%
“… Third, discourse is historical in that a text can only be understood in terms of its context, time, and place (cf. Wodak, 2001: 3 Sacks (1972;1992a;1992b) and expanded upon by a number of researchers (notably Hester & Eglin, 1997;Leudar & Nekvapil, 2000;Leudar, Marsland & Nekvapil, 2004;and Schegloff, 2007), MCA studies how people employ social categories -membership categorisation devices or labels -to organise themselves into specific groups that reflect their identities (cf. Zimmerman, 2007: 72).…”
Section: Critical Discourse Analysis (Cda)mentioning
confidence: 99%